Frequency Domain Spectroscopy Analysis of the Water Tree XLPE Cable - Whichakorn Sawatdimongkol; Phop Chancharoensook; Worachai Sawatdimongkol; Alisala Taylim; Amata Luangpol; Norasage Pattanadech (2022 9th International Conference on Condition Monitoring and Diagnosis (CMD), 2022)
Water tree is one type of insulation deterioration occurring in polymeric cables such as polyethylene, ethylene-propylene rubber, and cross-linked polyethylene (XLPE) caused by the existing impurities in the bulk insulation or imperfection of the semiconductive surface. Moreover, the water tree phenomenon affects the cable's overall lifetime and can be developed into an electrical tree, leading to the failure of the cable. Because of this, the evaluation of water trees becomes one of the most important factors in the condition assessment of the cable. This paper presents the comparison of the dielectric properties of 22 kV XLPE underground cable between aged and new (unused) cables. Furthermore, the water tree was detected in the aged cable. Besides, the evaluation of aged and new cables was performed by frequency-domain spectroscopy (FDS), which measures the insulation's complex capacitance and dissipation factors in the frequency domain. Then, the aged and new cables' complex capacitance and dissipation factor were compared. The test result found that the dissipation factor and imaginary part of the complex capacitance of the aged cable have a higher value than these of the new cable. More or less, the results show that FDS is one of the non-destructive testing methods suitable for assessing the condition of the cable insulation, which deteriorated by water tree.
Keywords: High voltage insulation and dielectric phenomena; Power Transformer Diagnostics and Insulation; Electrical Fault Detection and Protection